Using DNA to Locate the Ancestry of Today's Island Dogs of the Caribbean: The Case of the Bahamian Potcake - Fielding, William J.; Mundle, Marcia; Brown, Sarah K.; Sacks, Benjamin N. (International Journal of Bahamian Studies, 2014)
Dogs in The Bahamas have been documented since the time of Columbus, so dogs have been residents of the country for at least as long as our written records. While the term “potcake” has been associated with mongrel dogs in The Bahamas for some time; written references have been traced back only as far as 1970. Since then, the written word potcake has become relatively common. Potcakes, while reviled by some, are considered as quintessentially Bahamian by others. This paper attempts to determine if the potcake is unique to The Bahamas. Our analysis of potcake DNA from New Providence and Grand Bahama suggests that the importation of dogs has diluted the pool of any ancient potcake DNA to an extent, that the Bahamian potcake, if it ever existed, is now either extinct or highly admixed. Some implications for demystifying this Bahamian icon based upon the current welfare offered potcakes are proposed.